SUSTAINABILITY COMMUNICATION STRATEGY IN @EOS_INDONESIA TIKTOK CONTENT IN BUILDING ELECTRIC VEHICLE EDUCATION - Dwi Ajeng Sri Rahayu; Asrul Nur Iman (PT. Jurnal Center Indonesia Publisher, 2026)
The increasing use of electric vehicles in Indonesia is a step in the framework of transforming the transportation system to be more environmentally friendly to achieve the Net Zero Emission target of 2060. However, the increasing use of electric vehicles is not only due to technical and policy changes, but also communication efforts. This study attempts to analyze the sustainability communication strategy used by the TikTok account @eos_indonesia in providing education related to electric vehicles. This study uses a qualitative method with a content analysis approach, These methods consist of digital participatory observation and documentation, The data collection is an analysis of the TikTok account @eos_indonesia content data that will be taken with a time span of April 2025 - June 2026 according to the classification that has been made, the data collected includes: video content (visual, audio and narrative). and content analysis has stages, starting from determining the unit of information, data sampling, recoding or recoding data (coding), grouping based on certain categories until finally interpreting the meaning contained in the message content. The research results show that sustainability communication strategies are carried out through five approaches: providing environmental education, reducing the complexity of electric vehicle technology, storytelling based on user experience, digital visual persuasion, and combining economic and environmental benefits in every communication message. This study contributes to the field of digital communication and sustainability communication by demonstrating the potential effectiveness of social media as a public education platform towards green transportation transformation in Indonesia.